Investigating the Challenges of E-Learning in a Developing Institution of Higher Learning: A Hypothetical Approach - Agbenyegah, Albert Tchey; Dlamini, Bongani Innocent (Journal of Applied Business Research, 2019)
The popularity of e-learning (EL) largely infiltrated into every sector of South African institutions of higher learning. This growing interest in EL is due to the advent of rapid internet technologies. For decades, South African institutions of higher learning have accepted EL as a vital learning tool for the enhancement of learning and teaching within the higher education sector. However, there are countless challenges that continue to hinder learning and teaching activities. This study seeks to determine the relationships between various challenges and EL capabilities through stated hypotheses. The study is a descriptive, qualitative design aided by a quantitative approach that were applied to collect data. In total 150 full and part-time ICT students including four permanent ICT lecturers participated in the study. By means of statistical methods of descriptive, inferential statistics aided by independent t-tests, three stated hypotheses were formulated and tested. The study therefore, recommends that higher institutions of learning should increase investments in various EL programs including relevant ICT infrastructure development and also in levels of connectivity. The study further recommends that EL contents should be designed taking into account the cultural characteristics of students.